A Late Adolescent Girl with Rectal Duplication Cyst in Bangladesh: Case Report (Journal of Surgical Sciences, 2019)
Intestinal duplications, originally described in 1941, are congenital cystic lesions resemblingand associated with part of the gastrointestinal tract. Rectal duplication is the rarest of the allduplications and adolescence presentation of rectal duplication cyst is quite unusual whichis reported here. A 17 year female presented with right gluteal lump. She underwent surgeryand was found to have a smooth cystic mass, which was later found to be a Rectal Duplicationcyst in histopathology. High index of suspicion with other differentials can lead to earlydiagnosis and complete cure of the condition.Journal of Surgical Sciences (2017) Vol. 21 (1) :45-46